FOSSIL SCORPIONFLIES OF THE "SUBORDER" PARATRICHOPTERA (INSECTA: MECOPTERA) - Novokshonov V.G.; Sukacheva I.D. (My University, 2001)
The suborder Paratrichoptera (Mecoptera) is discarded as polyphyletic. The family Choristopsychidae Mart. is synonymized under Permochoristidae Till. The generic composition of the family Mesopsychidae Till. is revised. Eight new Mesozoic scorpionflies are described: Mesopsyche justa sp. nov., M. ordinata sp. nov., M. tortiva sp. nov., M. gentica sp. nov., Vitimopsyche torta gen. et sp. nov., Baissopsyche pura gen. et sp. nov. (Mesopsychidae), Mecaenigma viduum gen. et sp. nov., M. suspectum sp. nov. (Mecoptera incertae sedis).
Keywords: Mesozoic; Mesozoic; Мезозой